Socioscientific issues in the portuguese science curricula from the first to the sixth grade - Pessoa, Patrícia (2022)
The Socioscientific issues (SSI) approach has been proven to be effective in promoting scientific literacy. Although, little research has been done on the application of this approach at the early elementary school level. The few existing studies report that SSI-based learning is important because it allows students to connect scientific knowledge to social issues, laying a valid foundation for more complex reasoning and understanding in their future scientific learning. On the other hand, elementary school teachers feel more comfortable in implementing SSI in classroom because they usually teach across subjects. However, these teachers may face some concerns in implementing this approach, similar to those already reported by teachers at higher grade levels. Given this, it is important to identify in the curricula opportunities to explore SSI in order to be able to design ways of empowering elementary school teachers. To achieve this goal, in our work we i) conducted a literature review to inform the development of a framework to identify and categorize SSI, and ii) applied the framework as categories of analysis to identify opportunities to explore SSI in the Portuguese curriculum from 1st to 6th grade. Our findings shows that the Portuguese official documents present 33 opportunities for students to engage in SSI-based learning, most of them related to environmental issues and in smaller number healthrelated issues. These results may inform the development of future research and the development of educational proposals focused on these education levels.